Fast In‐Situ Optical Visualization of Carbon Nanotubes Assisted by Smoke. Issue 1 (2nd December 2021) - Li, Run; Jiang, Qinyuan; Wang, Fei; Shi, Xiaofei; Chen, Fengxiang; Huang, Ya; Wang, Baoshun; Zhang, Wenshuo; Wu, Xueke; Wei, Fei; Zhang, Rufan
Abstract: The fast visualization and manipulation of individual carbon nanotubes (CNTs) has always been a significant technology for their fundamental research. Here, a fast and facile approach is proposed to realize the optical observation of individual suspended CNTs and CNT networks under conventional optical microscopes with the assistance of tar nanodroplets from smoke. The nanodroplets deposited on CNTs render them with strong light scattering to visible light, thus making the CNTs visible under optical microscopes. This visualization method is controllable, environmentally friendly, low‐cost, and can be completed in just a few seconds in ambient conditions. Besides, the tar nanodroplets can be easily removed from the CNTs by laser irradiation. More importantly, the smoke sources are widely available and there are no strict requirements for operating conditions. This smoke‐assisted visualization method shows great potential in the fundamental research of CNTs. Abstract : A facile approach is proposed to realize the optical observation of suspended carbon nanotubes under optical microscopes with the assistance of smoke.